Exploring ground-state and ionization potentials of the H2CO...HNO dimers - Souza, Gabriel Luiz Cruz de; Peterson, Kirk Arnold (Universidade Federal de São Carlos, 2025)
In this work, we performed an investigation on the structures and ionization potentials (IPs) of the H2CO...HNO dimer. The ground-state properties of six conformations were explored using the coupled cluster with single, double, and perturbative triple excitations, CCSD(T), approach with large correlation consistent basis sets. Conformation III presented the strongest hydrogen-bonding interaction (with the NH...O distance being 2.016 Å) and was assigned as the most stable among the conformations. In addition, twelve lowest-lying IPs of all the H2CO...HNO conformations were determined using the equation-of-motion ionization potential coupled-cluster with single and double excitations method (EOMIP-CCSD) combined with correlation consistent basis sets, extrapolation to the complete basis set limit, and consideration of core correlation effects. The first IP of conformation III was determined to be 10.46 eV, while the corresponding values for conformations I and II were found as being lower than the value obtained for conformation III by 0.41 eV and 0.24 eV, respectively. These differences (that were also noticed for other low-lying IPs) may be helpful for the assignments of experimental results and, thus, it is expected that the outcomes from this work may serve as motivation for other experimental and theoretical investigations involving H2CO...HNO dimers (particularly studies that rely on the quantities obtained here).
Keywords: Ionization energies; H2CO...HNO dimers; CIENCIAS EXATAS E DA TERRA::QUIMICA; 4. Educação de Qualidade